1997
DOI: 10.1074/jbc.272.14.8861
|View full text |Cite
|
Sign up to set email alerts
|

A Familial Amyotrophic Lateral Sclerosis-associated A4V Cu,Zn-Superoxide Dismutase Mutant Has a Lower K for Hydrogen Peroxide

Abstract: Point mutations of Cu,Zn-superoxide dismutase (Cu,Zn-SOD) have been linked to familial amyotrophic lateral sclerosis (FALS). We reported that Cu,Zn-SOD can catalyze free radical generation and a FALS mutant, G93A, exhibits an enhanced free radical-generating activity, while its dismutation activity is identical to that of the wild-type enzyme (Yim, M. B., Kang, J.-H., Yim, H.-S., Kwak, H.-S., Chock, P. B., and Stadtman, E. R. (1996) Proc. Natl. Acad. Sci. U. S. A. 93, 5709 -5714). The A4V mutation is both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
98
2
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(106 citation statements)
references
References 22 publications
4
98
2
1
Order By: Relevance
“…ABTS •+ is a persistent radical which can be readily detected and identified by its characteristic EPR spectrum [29,30]. Fig.…”
Section: Epr Studymentioning
confidence: 99%
“…ABTS •+ is a persistent radical which can be readily detected and identified by its characteristic EPR spectrum [29,30]. Fig.…”
Section: Epr Studymentioning
confidence: 99%
“…In the presence of H202 and radical scavengers, especially with anionic character, both free 9 radicals and scavenger-derived radicals are produced (15,16). We also found that the free radical-generating function of several FALS-associated Cu,Zn-SOD mutants is enhanced relative to that of the wild-type enzyme, while the dismutation activities remain unchanged (17,18).…”
mentioning
confidence: 63%
“…In the presence of H202 and radical scavengers, especially with anionic character, both free 9 radicals and scavenger-derived radicals are produced (15, 16). We also found that the free radical-generating function of several FALS-associated Cu,Zn-SOD mutants is enhanced relative to that of the wild-type enzyme, while the dismutation activities remain unchanged (17,18).To monitor the production of free radicals, two spin traps, 5,5-dimethyl-l-pyrroline N-oxide (DMPO) and Ntert-butyl-c~-phenylnitrone (PBN), were used in our studies (15) to convert transient free radicals to stable free radicals adducts according to the following reactions:The nature of the trapped free radical was identified by EPR spectroscopy. When O2-" (dissolved KO 2 in dried dimethylsulfoxide) was added to the NaHCOJCO 2 buffer at pH 7.6 containing 100 mM DMPO, EPR OH adducts.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…It has been reported that the FALS mutants, G93A and A4V, exhibits an enhanced free radicalgenerating activity, while its dismutation activity is identical to that of the wild-type enzyme [12][13][14]. Previous results showed that the hydroxyl radical was generated in the reaction of human Cu,Zn-SOD with H202 [ 15].…”
Section: Resultsmentioning
confidence: 99%